Acts and Laws of His Majesties Colony of Rhode-Island, and Providence Plantations in America 86-87 (1179 [1719]) - (:unkn) unknown (My University, 1718)
That every Listed Soldier of the said Militia, shall be always provided with one good Musket, or Fuzee, the Barrel whereof not to be less than three foot and an half in length, to the satisfaction of the Commission Officers of the Company; also one pound of good Gunpowder, thirty Bullets, fit for his Gun, six good Flints, fit for Service; one good Sword, or Baionet, a Cartouch Box, ready
Keywords: REQUIRED POSSESSION